Current trend in offshore wind energy sector and material requirements for fatigue resistance improvement in large wind turbine support structures – A review. (March 2019) - Igwemezie, Victor; Mehmanparast, Ali; Kolios, Athanasios
Abstract: At present, the UK government is driving the survival of the wind energy industry by using interventions that encourage investment in the sector. The use of a Contract for Difference (CfD)/Strike price model by the UK government supports the wind industry and guarantees that wind energy generators have a stable premium over a period of 15–20 years; however, this may not last forever. The growth and stability of the wind industry will depend essentially on continued reductions in wind energy cost, even below that of fossil-fuel based energy sources. Huge cost reduction beyond the present strike price of £ 57.50/MWh for some projects to be delivered in 2022/2023 may be achieved quickly through efficient and optimized turbine support structure. Consequently, the offshore wind industry is currently making enormous efforts to upscale wind turbines (WTs) from 8 MW to 9.5MW, 10MW and then 12 MW HAWT (Horizontal Axis Wind Turbine). This level of upscaling no doubt creates tough challenges because the mass of the turbine increases linearly with the cube of the rotor radius. Monopiles having diameters larger than 7 m have been proposed, with a wall thickness section in the range of 70–110 mm. It is generally thought that Thermo-Mechanical Controlled Process (TMCP) steels are well suited for extra-large (XL-WTs). This paper reviews the present status of WTs and critically assesses the material factors in the structural integrity concerns that may confront the use of XL steel plates in the design of XL-WT support structures.